Movement in Math: A Look at Integrating Movement-Based Activities into a Kindergarten Math Classroom - Katelyn R Gonzales (Networks: An Online Journal for Teacher Research, 2024)
The purpose of this study was to examine what happens when movement-based mathematical activities are introduced into a kindergarten math curriculum and its implications on how kindergarteners engage during math time. Using surveys, observational and reflective data, and semi-structured interviews of students and my cooperating teacher, this study aimed to examine student and teacher perceptions of incorporating movement-activities. The movement activities served as form of play-based learning and relied on thorough planning and preparation. Through the constant-comparative method, I generated 12 level 1 and three level 2 codes from key themes and analyzed descriptive statistics for numerical data from my surveys. This study also strived to understand teachers’ feelings about incorporating movement-based activities into their regular math lessons.
Keywords: movement; gross motor activities; mathematics; kindergarten; play; play-based learning; engagement; early elementary; elementary; exercise; activity; teacher; learning; classroom; graph; addition; shapes; afternoon; counting